Pengaruh Layanan Informasi dengan Teknik Self Asessment untuk Memutuskan pada Karier Siswa Kelas 12 SMA Bandung Percut Sei Tuan - Sri Ulfa Hasibuan; Alfin Siregar; Irwan Irwan (Politeknik Kampar, 2025)
This study aims to determine the effect of information services using the self-assessment technique on students’ ability to make career decisions, as well as to analyze the extent to which such services influence students’ clarity and confidence in choosing a career path. The research method employed was quantitative, utilizing a quasi-experimental design with a non-equivalent control group. The study population consisted of 12th-grade students at SMA Bandung Medan for the 2024/2025 academic year, with a sample of 30 students divided into an experimental group (which received information services utilizing audio-visual media) and a control group (which received information services through question-and-answer discussions). Data collection techniques included interviews, documentation, and questionnaires that were assessed for validity and reliability. Data analysis involved normality tests, homogeneity tests, and hypothesis testing using the Paired-Samples T-Test with SPSS software. The results of the study indicate that information services using the self-assessment technique have a significant effect on the career decision-making ability of 12th-grade students at SMA Bandung Medan, Percut Sei Tuan District. Based on normality and homogeneity tests, the data were found to be normally distributed and homogeneous, thus meeting the requirements for parametric testing. The Paired Samples Test analysis produced a significance value of 0.000 (< 0.05), indicating a significant difference between the experimental group that received information services with the self-assessment technique through audio-visual media and the control group that only received information services through question-and-answer discussions. These findings demonstrate that self-assessment-based information services enhance students’ ability to recognize their own potential, leading to more accurate and rational career decisions. Furthermore, the results show that the self-assessment technique positively contributes to strengthening students’ clarity and confidence in their chosen career paths. Therefore, it can be concluded that the implementation of information services using the self-assessment technique is effective in helping students navigate the career decision-making process in a more directed, realistic, and self-reflective manner.